Implementation of The Savi Learning Model in Description Text Writing Skills: A Strategy to Improve Students' Writing Skills - Nurwan Patilima (Lingedu: Journal of Linguistics and Education, 2025)
Abstract: This study examines the effectiveness of the SAVI (Somatic, Auditory, Visual, Intellectual) Learning Model as a strategy to improve students' descriptive text writing skills. The limitations of students in choosing diction, composing effective descriptive sentences, and organizing ideas are the main obstacles. The SAVI model is implemented to activate all student learning modalities, especially through physical (somatic) and visual experiences to enrich descriptions. The research uses a two-cycle Class Action Research (PTK). Data was collected through observation of the learning process, product assessment of descriptive text writing, and student response questionnaires. The results showed a significant increase in the average value of descriptive text writing skills from the pre-action condition to Cycle II. This improvement proves that the SAVI Model is able to provide a holistic stimulus, effectively improving the creativity and quality of students' writing descriptions.